2003
DOI: 10.1097/01.jom.0000083038.56116.30
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs Associated With Fecal Occult Blood Test and Colonoscopy Use at a Worksite Colon Cancer Screening Program

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. Although regular screening can decrease morbidity and mortality from CRC, screening rates nationwide are very low. This descriptive study assessed beliefs associated with fecal occult blood test and colonoscopy use among participants of a worksite colon cancer screening program. Randomly selected employees, aged 40 and older, were mailed a survey on CRC screening-related beliefs. Instruments were tested for reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 42 publications
11
51
1
1
Order By: Relevance
“…This finding is consistent with a prior study which showed that the use of cancer screening services among women in this same population was lower due to differences in health insurance coverage for office visits (16). Potential barriers to CRC screening may include low consumer acceptance and beliefs, low provider recommendations, poor provider reimbursement, and lack of provider skill (3,21,22). Our study suggests another barrier to CRC screening: office visit cost-sharing.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with a prior study which showed that the use of cancer screening services among women in this same population was lower due to differences in health insurance coverage for office visits (16). Potential barriers to CRC screening may include low consumer acceptance and beliefs, low provider recommendations, poor provider reimbursement, and lack of provider skill (3,21,22). Our study suggests another barrier to CRC screening: office visit cost-sharing.…”
Section: Discussionsupporting
confidence: 90%
“…Four items were included that addressed two key references-family and doctor or health professional. For the current study, we substituted health professional for friends [used in the Vernon et al study (26)] as a key referent because several studies have shown physician recommendation to be one of the most important predictors of colorectal cancer screening adherence (13,18,22,24,(46)(47)(48)(49)(50)(51)(52)(53)(54) and because we wanted to show that the influence of the family and health professional forms one factor as hypothesized by Ajzen and Fishbein (42,55) and Cialdini and Trost (56).…”
Section: Methodsmentioning
confidence: 99%
“…The reliability and validity of belief scales used in this study had previously been established [13,14]; hence, few changes in the scales were needed for Korean cultural appropriateness. These findings are consistent with scale development and modification guidelines [8], which indicate that scale adaptation and modification rather than scale development are appropriate if constructs or item contents overlap but are slightly different.…”
Section: Discussionmentioning
confidence: 99%
“…Health belief scales used to measure susceptibility, benefits, barriers, and self-efficacy in the present study were adapted from Menon et al [13] after obtaining permission from the author. These scales have demonstrated good reliability, with Cronbach's alpha above .70.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation